9 Łódzka Brygada Obrony Terytorialnej: Współczesność – historia – tradycja (Księgarnia Akademicka Publishing, 2024)
THE 9TH ŁÓDŹ TERRITORIAL DEFENCE BRIGADE: THE PRESENT – HISTORY – TRADITION The book has several fundamental goals to fulfil. The first one is to showcase 9th Łódź Territorial Defence Brigade [9th ŁTDB] in a comprehensive way as a modern, thriving military unit. Another one is to holistically present the elements that build the ethos of 9th ŁTDB through creating collective memory and cultivating the tradition. The publication is also intended to encourage readers to learn more about the activities of the 9th ŁTDB operating in Łódź Province, its patron, Brigade General Stanisław Sojczyński “Warszyc” and the troops of the Home Army and the Polish Underground Army, whose tradition the brigade inherited.